Phosphodiesterases maintain signaling fidelity via compartmentalization of cyclic nucleotides. - Lomas, O; Zaccolo, M (American Physiological Society, 2014)
Novel technological advances have improved our understanding of how cyclic nucleotides are able to convey signals faithfully between cellular compartments. Phosphodiesterases play a crucial role in shaping these signals in health and disease. The concept of compartmentalization is guiding the search for therapies that have the potential to offer greater efficacy and tolerability compared with current treatments.